Isolation and Characterization of Poly-3-hydroxybutyrate (PHB)-producing Bacteria from some Municipal Waste within Maiduguri Borno State Nigeria (Journal of Environmental Bioremediation and Toxicology, 2022)
The present work was conducted to isolate, screen and identify polyhydroxybutyrate (PHB)-producing bacteria from municipal wastes. Samples were collected from dumping sites of Maiduguri Borno State and were checked for their bacterial population using nutrient agar and PHB Detection agar (PDA). A total of 20 PHB-producing bacteria were isolated and identified. Of the total, four of the isolates were found to be from Paenibacillus spp. while the remaining 16 were Bacillus spp. Isolates from Ngomari Custin denoted as NC 5, 2; NC 7, and NC 5A were suspected to be Paenibacillus favisporus, Bacillus lentus, and Bacillus firmus respectively while others of NC 7A X, NC 6A and NC 7A Y of the same site were all found to be Bacillus smithii. Isolates from Old Maiduguri Graveyard denoted as OMG 5X, OMG 7, OMG 6 and OMG 5A were all found to be Bacillus smithii. The isolates from Flour Mill Area denoted as FMA 5A, FMA 6A, FMA Y, and FMA7B were found to be Bacillus smithii, Paenibacillus nanensis, Bacillus acidiceler and Paenibacillus septentrionalis respectively. On the other hand, isolates from Ramat Square site denoted as RS 6,2; RS 6A, RS 5, RS 7,2 were registered as Bacillus nealsonii, Paenibacillus cookie, Bacillus firmus and Bacillus megaterium respectively. Those of RS 5B and RS 7A of the same sample site were both Bacillus acidiceler and their granules were stained by Nile Blue A staining and observed under the fluorescence microscope and were classified for the extent of their PHB production based on the intensity of fluorescence emitted under the microscopy. NC 7 produced the highest PHB yield compared to all other isolates. Hence, municipal wastes are a rich reservoir of PHB-producing bacteria and can readily produce (PHB), which has enormous advantages over petroleum-based polymers by means of cost effectiveness and eco-friendliness
Keywords: Isolation; Bacteria; Bioplastic; Polyhydroxybutyrate (PHB); Municipal waste